Legal Study of Iran's Perspective on One Belt One Road Initiative as a China Economic Expansion Strategy - Adawiyah Nasution; Haya Qonita; Farrel Maulana; Safira Prima Indira (LEGAL BRIEF, 2022)
The unique thing that happened was that China became a party that could cooperate with countries in the Middle East even though these countries were at war with each other. China became a great support for Iran when the United States decided to launch an embargo on Iran, but China in fact has a strong cooperative relationship with Saudi Arabia which is a rival to Iran. In terms of the feud between Qatar and Saudi Arabia, China was able to become a mediator by using the CASCF forum in Beijing. When Saudi Arabia launched an economic embargo on Qatar, the steps taken by China were to increase exports and imports so that it could replace the United States, which had previously been a source of Qatar's imports. China is able to negotiate with countries in the region by offering the establishment of a more effective cooperative relationship, which is valid for a long period of time in the diplomatic, security, and economic areas. China's economic expansion has been achieved by establishing good bilateral relations with Middle Eastern countries, although there are big differences in the geopolitical interests of each country. The purpose of this study is to examine China's Strategy; Economic Expansion in the Middle East Region, and Iran's Perspective on the One Belt On Road Initiative, with legal analysis methods and descriptive analysis related to the themes in this paper. China's economic expansion has been achieved by establishing good bilateral relations with Middle Eastern countries, although there are big differences in the geopolitical interests of each country. The purpose of this study is to examine China's Strategy; Economic Expansion in the Middle East Region, and Iran's Perspective on the One Belt On Road Initiative, with legal analysis methods and descriptive analysis related to the themes in this paper. China's economic expansion has been successfully achieved by establishing good bilateral relations with Middle Eastern countries, even though there are big differences in the geopolitical interests of each country. The purpose of this study is to examine China's Strategy; Economic Expansion in the Middle East Region, and Iran's Perspective on the One Belt On Road Initiative, with legal analysis methods and descriptive analysis related to the themes in this paper.